Interactive effect of weeding regimes, rice cultivars, and seeding rates influence the rice-weed competition under dry direct-seeded condition - Ahmed, Sharif; Alam, M. Jahangir; Hossain, Akbar; Islam, A. K. M. Mominul; Awan, Tahir H.; Soufan, Walid; Qahtan, Ahmed Ali; Okla, Mohmmad K.; EL Sabagh, Ayman (MDPI, 2020)
Dry direct-seeded rice (Oryza sativa L.), a climate-smart and resource-efficient (labor and water) rice production technology is gaining popularity in many parts of Asian countries; however, weeds are the major constraints for its early establishment and optimum productivity. Chemical weed management is effective, rapid, and also decreases weed management costs in dry direct-seeded rice (DSR) system; however, chemical use for weed management have a negative effect on the environment and also have human health hazards. Therefore, integrated weed management (IWM) is the best option for the sustainability of rice production under the DSR system. Improving competitiveness against weeds, weed-competitive rice cultivars, and high seeding rates were found to be the most promising IWM strategies in DSR. In this context, a field study was conducted to evaluate the weed competitiveness of rice cultivars and seeding rates on the performance of aus rice in dry direct-seeded systems in Bangladesh. Three inbred rice cultivars (CV), namely “BRRI dhan26”, “BRRI dhan48”, and “BRRI dhan55”, and one hybrid cultivar, “Arize” were tested in a seeding rate (SR) of 20, 40, and 80 kg ha−1 under two weeding regimes (WR) of weed-free and partially-weedy. Rice grain yield was strongly affected (p < 0.01) by the interactions of WR, CV, and SR. In weed-free conditions, the yield of all three inbred cultivars was increased up to SR of 40 kg ha−1 and for the hybrid cultivar, up to SR of 20 kg ha−1, and with further increment of SR, there was no yield advantage. Conversely, under partially weedy conditions, the yield of three inbred cultivars increased up to SR of 80 kg ha−1; however, for the hybrid cultivar, this increment was up to SR of 40 kg ha−1 and thereafter, no yield gain. In weedy conditions, the higher SR compensates for the yield losses by increasing the competitiveness of rice with weeds. Across SR, the hybrid cultivar had a significantly (p < 0.01) higher weed competitive index (WCI) than all the inbred cultivars and the highest SR always had a higher WCI.